P4VP and oligo(phenylenevinylene)-perylenebisimide mixed donor-acceptor supramolecular comb polymer complexes with improved charge carrier mobility - Saibal, B.; Chithiravel, Sundaresan; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
Random donor-acceptor (D-A) supramolecular comb polymers were formed when hydroxyl functionalized donor and acceptor small molecules based on Oligo(phenylenevinylene) (named OPVCN-OH) and Perylenebisimide (named UPBI-PDP), respectively, were complexed with Poly(4-vinyl pyridine) (P4VP). A series of random D-A supramolecular comb polymers were formed by varying the ratios of UPBI-PDP and OPVCN-OH with P4VP. A 100% P4VP-donor polymer complex [P4VP(OPV1.00)] and a 100% P4VP-acceptor polymer complex [P4VP(UPBI1.00)] were also synthesized and characterized. Complex formation was confirmed by FT-IR and H-1 NMR spectroscopy. Solid state structural studies carried out using small angle X-ray scattering and wide angle X-ray diffraction experiments revealed altered packing of the D and A molecules in the complexes. Transmission electron microscopy images showed lamellar structures in the <10 nm scale for the P4VP(OPV1.00), P4VP(UPBI1.00), and mixed P4VP (D-A) complexes. The effect of the nanoscopic D-A self-assembly on the bulk mobility of the materials was probed using SCLC measurements. The mixed D-A random complexes exhibited ambipolar charge transport characteristics with higher values for the average bulk hole mobility estimate. P4VP(OPV0.25+UPBI0.75) exhibited an average hole mobility in the order of 10(-2) cm(2) V-1 s(-1) and electron mobility 10(-5) cm(2) V-1 s(-1). (C) 2016 Wiley Periodicals, Inc.
Keywords: donor-acceptor; oligo(phenylenevinylene); P4VP; Perylenebisimide; Self-assembly; structure-property relations; supramolecular comb polymer; supramolecular structures

Liquid crystalline supramolecular crosslinked polymer complexes of ditopic rylenebisimides and P4VP - Saibal, B.; Narayan, Rekha; Chithiravel, S.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Perylenebisimide and naphthalenebisimide (PBIPDP and NBI-PDP) end functionalized with pentadecyl phenol is designed as ditopic hydrogen bonding acceptors to form supramolecular crosslinked network with poly(4-vinyl pyridine) (P4VP). The pristine PBI-PDP has been grown as single crystals from DCM-MeOH (dichloromethane-methanol) mixture at room temperature, which revealed a P21 space group. Noticeably, the pentadecyl alkyl chain shields the aromatic perylene core on both sides resulting in the absence of p-p interaction in single-crystal assembly. The naphthalenebisimide derivative exhibits thermotropic liquid crystalline behavior, while both the molecules exhibits lyotropic liquid crystalline phases in tetrahydrofuran (THF), which were characterized using a combination of differential scanning calorimeter, X-ray diffraction, and polarized light microscopy. The hydrogen-bonded complex of both the rylenebisimides with P4VP preserves the mesomorphic properties in THF. The electron transport mobility measured by space charge limited current measurements reveals a two orders of magnitude increase in the charge transport in the P4VP complex compared to that of the pristine molecule. The average electron mobility obtained is mu(e, avg): 10(-3) cm(2)/Vs for P4VP-PBI compared to mu(e, avg): 10(-5) cm(2)/Vs for pristine PBI derivative. (C) 2017 Wiley Periodicals, Inc.
Keywords: crystal structures; ditopic rylenebisimide; hydrogen bonding; lyotropic liquid crystal; P4VP; Self-assembly; supramolecular crosslink; supramolecular structures